2020
DOI: 10.3390/ijerph17072415
|View full text |Cite
|
Sign up to set email alerts
|

High Particulate Matter Burden of Cigarettes from the United Arab Emirates and Germany: Are There Country-Specific Differences?

Abstract: Although the big tobacco companies offer the same cigarette brands across countries, little is known about the potential regional differences of the particulate matter (PM) emissions of apparently equal brands. PM emissions of three cigarette brands (Marlboro Gold, Winston Red resp. Classic, Parliament Platinum resp. Night Blue) from the United Arab Emirates (UAE) and Germany were analysed. Second-hand smoke was produced in a 2.88 m3 measuring cabin by an automatic environmental tobacco smoke emitter. PM size … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…This difference is most probably caused by the larger interior volume of the car (3.709 m 3 ). The over 90-fold increase of PM 10 , PM 2.5 , and PM 1 under C1 compared to baseline measurements was expectable, as previous studies have already shown extremely high concentrations of PM in confined spaces 37 39 . Measured PM concentrations of C2 to C7 compared to C1 were significantly lower (see Supplementary Table S2 online).…”
Section: Discussionmentioning
confidence: 63%
“…This difference is most probably caused by the larger interior volume of the car (3.709 m 3 ). The over 90-fold increase of PM 10 , PM 2.5 , and PM 1 under C1 compared to baseline measurements was expectable, as previous studies have already shown extremely high concentrations of PM in confined spaces 37 39 . Measured PM concentrations of C2 to C7 compared to C1 were significantly lower (see Supplementary Table S2 online).…”
Section: Discussionmentioning
confidence: 63%
“…The concentrations of NO, NO 2 , and NO x in SHS were measured of nine commercial cigarette brands (named cigarette A to I) and the 3R4F reference cigarette (Kentucky Tobacco Research and Development Center, University of Kentucky, USA) 26 . As the measurements took place during two PM investigations, the reference cigarettes (RC) were termed RC1 24 and RC2 25 . The cigarette brands A, C, and E were bought at the International Airport of Dubai, United Arab Emirates (UAE), while the brands B, D, and F were from the International Airport of Frankfurt, Germany 25 .…”
Section: Methodsmentioning
confidence: 99%
“…As the measurements took place during two PM investigations, the reference cigarettes (RC) were termed RC1 24 and RC2 25 . The cigarette brands A, C, and E were bought at the International Airport of Dubai, United Arab Emirates (UAE), while the brands B, D, and F were from the International Airport of Frankfurt, Germany 25 . Additionally, three mentholated cigarette brands (G, H, I) were tested, purchased at the central station, Frankfurt, Germany 24 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations